Age-related upregulation of perineuronal nets on inferior collicular cells that project to the cochlear nucleus - Almassri, Laila S.; Ohl, Andrew P.; Iafrate, Milena C.; Wade, Aidan D.; Tokar, Nick J.; Mafi, Amir M.; Beebe, Nichole L.; Young, Jesse W.; Mellott, Jeffrey G. (Frontiers in Aging Neuroscience, 2023)
Introduction Disruptions to the balance of excitation and inhibition in the inferior colliculus (IC) occur during aging and underlie various aspects of hearing loss. Specifically, the age-related alteration to GABAergic neurotransmission in the IC likely contributes to the poorer temporal precision characteristic of presbycusis. Perineuronal nets (PNs), a specialized form of the extracellular matrix, maintain excitatory/inhibitory synaptic environments and reduce structural plasticity. We sought to determine whether PNs increasingly surround cell populations in the aged IC that comprise excitatory descending projections to the cochlear nucleus. Method We combined Wisteria floribunda agglutinin (WFA) staining for PNs with retrograde tract-tracing in three age groups of Fischer Brown Norway (FBN) rats. Results The data demonstrate that the percentage of IC-CN cells with a PN doubles from ~10% at young age to ~20% at old age. This was true in both lemniscal and non-lemniscal IC. Discussion Furthermore, the increase of PNs occurred on IC cells that make both ipsilateral and contralateral descending projections to the CN. These results indicate that reduced structural plasticity in the elderly IC-CN pathway, affecting excitatory/inhibitory balance and, potentially, may lead to reduced temporal precision associated with presbycusis.